GIL Top Policy Lessons on Empowering Women Entrepreneurs - World Bank (World Bank, Washington, DC, 2020)
Women make up more than half of the total number of entrepreneurs in Africa. Yet, on average, for every dollar of profits men entrepreneurs earn, women entrepreneurs earn 66 cents. Supporting women to grow their firms would translate into higher economic growth for Sub-Saharan Africa.